Endocrine tumors of the gastrointestinal tract and pancreas:grading, tumor size and proliferation index do not predict malignant behavior - Papadimitriou John C; Drachenberg Cinthia B; Alexiev Borislav A (BMC, 2007)
Abstract Context Gastrointestinal and pancreatic (GIP) endocrine tumors (ETs) have been regarded as slow growing neoplasms with distinct morphologic characteristics that behave less aggressively than carcinomas. The malignant potential of these tumors is difficult to predict. Objective To evaluate prognostic parameters, namely tumor size, tumor grade, and Ki-67 index in relationship to metastatic behavior of GIP ETs. Design Biopsies and surgical specimens from 38 patients with GIP ETs were selected. The study group comprised 16 males and 22 females (mean age 62.6 years; range 24-91). Formalin-fixed, paraffin-embedded tissue sections were stained with H&E, synaptophysin, chromogranin A, and Ki-67. Ki-67 index was evaluated using ChromaVision Automated Assisted Image Analysis software. Proliferative index was compared to tumor grade, and the degree of associations between tumor size, tumor grade, Ki-67 index and metastatic behavior of GIP ETs were evaluated. Results Fifteen of the twenty-two (68.18%) surgically staged neoplasms presented with peritoneal dissemination, lymphogeneous, and/or hematogeneous metastases. Nine of the metastatic tumors were G1 (9/13, or 69.23%), 5 were G2 (5/7, or 71.42%), and 1 - G3 (1/2, or 50%). Overall, 10/15 (66.66%) metastatic tumors showed < 2% Ki-67 immunoreactivity. Four ileal ETs had a synchronous malignancy. No significant correlation was found to exist between tumor grade and Ki-67 index as well as between tumor size, tumor grade, Ki-67 index and metastatic behavior. Conclusion The findings suggest that tumor size, tumor grade and Ki-67 index do not accurately predict malignant behavior of GIP ETs.